2018
DOI: 10.1371/journal.ppat.1007107
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-CpG-binding (SmMBD2/3) and chromobox (SmCBX) proteins are required for neoblast proliferation and oviposition in the parasitic blood fluke Schistosoma mansoni

Abstract: While schistosomiasis remains a significant health problem in low to middle income countries, it also represents a recently recognised threat to more economically-developed regions. Until a vaccine is developed, this neglected infectious disease is primarily controlled by praziquantel, a drug with a currently unknown mechanism of action. By further elucidating how Schistosoma molecular components cooperate to regulate parasite developmental processes, next generation targets will be identified. Here, we contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 71 publications
(107 reference statements)
3
14
0
Order By: Relevance
“…These proliferation defects are comparable to that observed in Hslsd1-expressing neural stem cells treated with the LSD1 inhibitors pargyline or tranylcypromine [59] and support previous findings confirming that Smlsd1 is also expressed in rapidly dividing cells throughout the parasite [78]. Smmbd2/3 (encoding an epigenetic reader of 5-methylcytosine) and Smcbx (encoding an epigenetic reader of methyl lysine) are also co-expressed in proliferative schistosome cells (h2b+); similar to SmLSD1 inhibition, knockdown of either reader results in reduced neoblast proliferation [79]. When additionally considered alongside neoblast proliferation defects found in adult schistosomes treated with 5-azacytidine (a DNA methyltransferase inhibitor [15,80]), epigenetic processes are rapidly emerging as essential regulators of schistosome stem cell biology.…”
Section: Discussionsupporting
confidence: 87%
“…These proliferation defects are comparable to that observed in Hslsd1-expressing neural stem cells treated with the LSD1 inhibitors pargyline or tranylcypromine [59] and support previous findings confirming that Smlsd1 is also expressed in rapidly dividing cells throughout the parasite [78]. Smmbd2/3 (encoding an epigenetic reader of 5-methylcytosine) and Smcbx (encoding an epigenetic reader of methyl lysine) are also co-expressed in proliferative schistosome cells (h2b+); similar to SmLSD1 inhibition, knockdown of either reader results in reduced neoblast proliferation [79]. When additionally considered alongside neoblast proliferation defects found in adult schistosomes treated with 5-azacytidine (a DNA methyltransferase inhibitor [15,80]), epigenetic processes are rapidly emerging as essential regulators of schistosome stem cell biology.…”
Section: Discussionsupporting
confidence: 87%
“…SmMBD expression levels were lower in male parasites recovered from knockout animals than in those recovered from wild-type mice. This gene has been linked to normal egg production and number of eggs produced [20], and our EBi3 -/-I mice eliminated smaller quantities of eggs in feces. SmMBD forms part of the NuRD repression complex along with the HDAC8 enzyme [42].…”
Section: Discussionmentioning
confidence: 75%
“…MBD methyl CpG binding domain is a protein that binds to methylated cytosines, and S. mansoni expressed it at all stages of the parasite's life cycle including both sexes. In the same approach the authors found that this protein has nuclear localization only and relates to oviposition [20]. Previous studies identified 17 USP orthologs in S. mansoni, by homology with 56 USPs present in H. sapiens, it was detected that the expression of these USPs is altered in stages of egg, cercariae, schistosomula and adult worms, reflecting a recycling of proteins used by the parasite during the evolutionary stage transition [21].…”
mentioning
confidence: 85%
“…Adult S. mansoni worms were cultured (as described above) for 72 h in a sub lethal concentration of 700015 (10 μM). After 72 h, a 1 μL aliquot of 10 mM EdU was added to the culture media and incubated for a further 24 h. Worms were subsequently collected and fixed as described previously ( Collins et al, 2013 ; Geyer et al, 2018 ). Anterior regions of both sexes were imaged on a Leica TCS SP5II confocal microscope using a 40× lens.…”
Section: Methodsmentioning
confidence: 99%